OPTIMIZATION OF LANTAS DIKMAS IN REDUCE TRAFFIC ACCIDENT RATE BY SALATIGA - naomi harahap (Advances in Police Science Research Journal, 2022)
ABSTRACTOPTIMIZATION OF LANTAS DIKMAS IN REDUCE TRAFFIC ACCIDENT RATE BY SALATIGAPOLICE SATLANTAS NAOMI OLINNA HARAHAP, 18.228, Accident is an incident on the road that is not suspected to involve a vehicle or road user resulting in loss of life or property. Traffic accidents are caused by various things, one of which is the quality of the driver, the feasibility of motorized vehicles, and the condition of infrastructure that does not meet safety standards. Satlantas Polres Salatiga are expected to be able to reduce the number of traffic accidents by using social methods, namely by giving an appeal to the publicKamsel, and the Binluh concept with data collection techniques through interviews, and observations.So, based on the results of this study, it was found that social education in reducing the number of traffic accidents is still not optimal because it is motivated by several factors, both internal and external factors that affect the implementation of the traffic education. Analyzed by using the SDO Theory explaining the implementation of direct social services in reducing the number of traffic accidents and then using the Communication Theory and Binluh Concept which describes the implementation of the direct social education to the community is to provide an appeal or socialization to the public regarding traffic rules with the aim of the community getting education about safety in traffic. cross. Keywords: Traffic Accident, Optimization, Traffic Dikmas